The Concept of Utang Na Loob Among Filipino Working Millenials - Renz Marion Gavino; Alyssa Mae Donato; Gabrielle Vera Panotan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research study explored the perceptions and experiences of Filipino working millennials regarding the concept of utang na loob. Utang na loob. It is a distinct Filipino value that refers to the debt of goodwill and reciprocity acquired when one person assists another. The study used a purposive sampling technique to identify Filipino working millennials, ages 26-41 years old from Tuguegarao City, Cagayan, as informants. Data on the participants' perceptions and experiences of utang na loob were collected through semi-structured interviews. Through qualitative analysis, significant findings emerged within two central themes and various sub-themes. Through the analysis of recurring themes, it was found that utang na loob among millennials reflects their evolving values and adaptation to contemporary contexts. It goes beyond gratitude, emphasizing positive change and meaningful experiences. Millennials extend utang na loob to various relationships, including mentors, colleagues, and strangers. Recommendations include cultural education for millennials, supportive work environments, integrating utang na loob in educational institutions, fostering open communication within families, and conducting further research on the cultural, psychological, and technological aspects of utang na loob. These findings enhance the understanding of utang na loob and offer insights for interventions that promote well-being and social harmony